أساليب إدارة الصراع التنظيمي في المؤسسة الجزائرية - طعم الله, زينب; بولهواش, عمر (جامعة الوادي - University of Eloued, 2020)
ملخص: نهدف من خلال مقالنا هذا إلى الوقوف على إدارة الصراع التنظيمي بالمؤسسات الجزائرية، باعتبار أنّ ظاهرة الصراع في انتشار واسع وشكلت صعوبات كثيرة للعديد من المؤسسات، وأدت إلى عرقلة نشاط بعض المؤسسات، خاصة في ظل الظروف الاجتماعية والاقتصادية الراهنة والتي تعيشها بلادنا. لذلك قمنا بدراسة ميدانية بمؤسسة الـ كناس لمعرفة الأساليب التي تتبعها الإدارة لحل الصراعات التنظيمية التي تنشأ بالمؤسسة، من خلال استطلاع رأي 67 موظفا من موظفيها بولاية الطارف. Abstract: In this article, we seek to identify the management of organizational conflicts in Algerian institutions, considering that the phenomenon of conflicts is widespread and that it has posed numerous difficulties for many institutions and has led to obstruction of the activity. Certain institutions, especially in .the current social and economic conditions in our country Therefore, we conducted a field study at the CNAS to determine the methods used by the administration to .resolve the organizational conflicts generated, by interviewing 67 of its employees in wilaya of El Tarf.
مقال
Keywords: الصراع ; الصراع التنظيمي ; إدارة الصراع; conflict, organizational conflict, conflict management